Distribution Pattern of Malignancy in the Oncology Department of 59 Bangabandhu Sheikh Mujib Medical University 2005 (Bangladesh Oncology Journal, 2009)
This study was carried out in the Department of Oncology of Bangabandhu Sheikh Mujib Medical University from 1st January 2005 to 31st December 2005. A total number of 1107 cancer patients were included, of them 72% were smoker, 500 were male and 607 were female. So the male to female ratio was 1: 1.21. Highest incidence of malignancy was observed in the age of 46 to 60. Top five malignancies in female like- Breast, Cervix, Ovary, Gall Bladder, Stomach. Top five malignancies in male like- Lung, Stomach, Liver, Lymphoma, and Colon. (Bang. Onc. J. 2009; 4 (2) : 59-62)